Awareness towards chain of custody certification in Africa: the case of Ghana - Attah, Alhassan; Ioras, Florin; Ratnasingam, Jegatheswaran; Abrudan, Ioan Vasile (University of Agricultural Sciences and Veterinary Medicine, Cluj-Napoca, 2010)
Forest certification was introduced in the early 1990s to address concerns of deforestation and forest degradation and to promote the maintenance of biological diversity, especially in the tropics. Initially pushed by environmental groups, it quickly evolved as a potential instrument to promote sustainable forest management (SFM). To date about 126,000 ha of forests have been certified by the different certification schemes in Africa, despite Africa accounting for 17% of the World’s forest cover. This has been due to the lack of awareness on forest certification and the low standards of forest management in the tropics. The authors conducted a survey of representative stakeholders, in particular export timber firms in Ghana to identify why Chain of Custody certification in the Ghana Timber sector remains undeveloped. A number of 103 stakeholders were consulted. Results collated indicate that the readiness to adopt chain of custody certification among the sector was low. The lack of a national scheme was cited as the primary reasons deterring the sector from adopting certification.